Sejarah dan Peran Dinasti Abbasiyyah antara Tahun 750 Hingga 1258 M dalam Peradaban Islam - Riskiyanda Wulandari; Nadia Febriyanti; Hermalisa Hermalisa; Ninda Audiska; Icha Fadillah Putri; Tria Desfika; Sirojul Fuadi (Jurnal Budi Pekerti Agama Islam, 2025)
The Abbasid dynasty was one of the most influential Islamic caliphates and left a long legacy in the development of world civilization. Established in 750 AD and ending in 1258 AD, the Abbasid period is known as the Golden Age of Islam due to its extraordinary progress in various fields, including politics, economics, and science. This study aims to examine how the Abbasid political and economic policies and the development of science that took place during that period were able to contribute significantly to the progress of global civilization. This study uses a qualitative method with a descriptive-historical approach through the study of relevant literature in the last five years. The results of the study indicate that political stability and a structured bureaucratic system provided a strong foundation for economic growth and intellectual progress. The Abbasid government established a center of knowledge in Baghdad known as Baitul Hikmah (House of Wisdom). Here, scientists from various religious and cultural backgrounds gathered to translate, develop, and disseminate knowledge from Greek, Persian, Indian, and other scientific traditions into the Islamic world. Some of the great figures who emerged during this period included Al-Khwarizmi (mathematics), Ibn Sina (medicine and philosophy), and Jabir Ibn Hayyan (chemistry). Their discoveries and work became the foundation for modern science. However, the glory of the Abbasids slowly declined due to internal conflicts, power struggles, and the weakening of the caliph's authority. The peak of the fall occurred when Baghdad was attacked and destroyed by the Mongols in 1258 AD. However, the intellectual and cultural heritage of the Abbasid dynasty continues to have an important influence on the development of world science and civilization to this day.